Application of the Palla? vibrating mill in ultra fine grinding circuits - Synopsis - K. Andres (The Southern African Institute of Mining and Metallurgy, 2010)
This paper presents the vibrating mill technology and summarizes the grinding principle of ultra fine grinding. In addition, a variety of operations is described and the benefits of these different operating modes? product size and efficiency are specified. A case study of an industrial application is presented to show the integration of vibrating mills into grinding circuits. The primary focus is the overall process scheme of this technology, the installation and operating costs, as well as the design parameters required for best performance. The vibrating mill can be used in a wide range of applications for process engineering duties. For a wide range of applications, from soft to extremely hard products, which require ultra fine grinding, surface activation or homogenization, the vibrating mill is well proven. Due to its easy operation, versatility and operation efficiency, the PALLA? vibrating mill gains in importance in the mineral processing industry. Keywords: Coal, comminution, grinding, mineral processing